Impact of the light microclimate on photosynthetic activity of grape berry (Vitis vinifera): insights for radiation absorption mitigations' measures - Garrido, Andreia (2018)
IPCC's predicted rise in mean temperatures, increase in the frequency of summer heat waves and decrease in soil water availability for the Mediterranean regions will have an impact on foliar and fruit photosynthesis. But mitigation measures aiming reducing radiation absorption by the vine canopy may pose light limitations to grape berry photosynthesis. This work focused on the influence of the light level of the canopy microenvironment where clusters develop on the photosynthetic competence of grape berry tissues (exocarp and seed integument) throughout fruit growing season by imaging PAM fluorometry. Clusters from low (LL), medium (ML) and high light (HL) microclimates were sampled from green to mature stages. Both tissues showed high maximum quantum efficiency (Fv/Fm) and photosynthetic capacity (ETRm) at the green stage, exocarp extending to mature stages while seed photosynthetic activity was more restricted to green stage. The light microclimate had a significant effect on the photosynthesis of both tissues but also in their photosynthetic phenotypes along the season. In LL, both tissues showed lower activity in all stages, higher susceptibility to photoinhibition and lack of response to short-term light acclimation; ML and HL grapes adjust their activity peaking at different light intensities, were more responsive to light changing conditions, recover better from high light. Overall, our results suggest that not only light/temperature stress conditions imposed by climate changes but also viticulture practices causing changes in canopy light microclimates may have significant impacts on grape berry photosynthesis and hence in fruit development and quality.